1982
DOI: 10.1037/0022-0167.29.5.468
|View full text |Cite
|
Sign up to set email alerts
|

Resolving decisional conflict by Gestalt two-chair dialogue: Relating process to outcome.

Abstract: Thirty-one clients completed a six-week program using Gestalt two-chair dialogue to work on intrapsychic conflict related to the making of a decision. The clients were classified as resolvers or nonresolvers based on a pattern of in-session process indicators. The resolvers were identified as clients who had manifested three components of a proposed model of conflict resolution:. the expression of criticism by one part of the personality, the expression of feeling and wants by another, and the softening in att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 24 publications
1
58
1
3
Order By: Relevance
“…When compared to CCT, two previous studies have favoured EFT as more effective than CCT for depressed clients (Goldman, Greenberg, & Angus, ; Greenberg & Watson, ). Also, particularly in the investigations of the two‐chair dialogue (Greenberg & Dompierre, ; Greenberg & Webster, ), the results suggest that this intervention reduces symptoms of distress and more so than empathic reflection alone. Furthermore, Greenberg and Clarke () found that the two‐chair dialogue was associated with better emotional processing.…”
Section: Introductionmentioning
confidence: 92%
“…When compared to CCT, two previous studies have favoured EFT as more effective than CCT for depressed clients (Goldman, Greenberg, & Angus, ; Greenberg & Watson, ). Also, particularly in the investigations of the two‐chair dialogue (Greenberg & Dompierre, ; Greenberg & Webster, ), the results suggest that this intervention reduces symptoms of distress and more so than empathic reflection alone. Furthermore, Greenberg and Clarke () found that the two‐chair dialogue was associated with better emotional processing.…”
Section: Introductionmentioning
confidence: 92%
“…For example, evidence suggests that surrogates with higher decisional conflict who later question their treatment decisions have worse psychological outcomes (2). In addition, those who resolve their decisional conflict have significantly less anxiety at follow-up than nonresolvers (27).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, intensive analyses of two-chair and empty-chair dialogue tasks in EFT and Gestalt psychotherapy has led to the development of performance models that specify and empirically validate key components necessary for task resolution (Greenberg, 1979(Greenberg, , 1983Greenberg & Foerster, 1996;Greenberg & Malcolm, 2002;Greenberg & Webster, 1982;Pascual-Leone, 2009;Sicoli & Hallberg, 1998;Whelton & Greenberg, 2000).…”
Section: Quality Of Clients' Emotional Engagementmentioning
confidence: 99%